A novel channel access algorithm based on clusters and MAB model in cognitive vehicular network - Fei PENG; Guoan ZHANG; Yuqi YANG (Dianxin kexue)
Considering the cognitive channel access problem of vehicle nodes in cognitive vehicular networks with heavy traffic environment,a channel access algorithm called clusters-UCB which based on clusters and MAB model was proposed.The cooperation of cluster members could improve perception accuracy and enhance the learning speed.And using improved multi-user UCB algorithm,cluster heads could quickly search out the optimal channel in a distributed way,which could make the network asymptotically achieve the optimal slot throughput.Simulation results show that with respect to UCB algorithm and ε-greedy algorithm,the regret of the proposed algorithm is lower and the speed of approaching logarithmic form is faster.What's more,clusters-UCB can effectively reduce the number of collisions when clusters access the cognitive channels,ensuring the fairness of the channel access and achieving better slot throughput.